The Role and Challenges of Arie Dwi Ningsih in the Development of Islamic Educational Institutions in Deli Serdang, North Sumatra - Sihombing, Arfiana; Azizah Hanum OK; Salminawati (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research aims to analyze the biography, contributions, and challenges faced by Arie Dwi Ningsih in the development of Islamic educational institutions in Deli Serdang. The research method used in this study is a qualitative research method, with a character study approach. The data collection techniques used are interviews, observations, and document studies. The data analysis techniques used in this research are historical continuity and systematic report writing. The research findings revealed that Arie Dwi Ningsih is an educational figure who has made significant contributions to the development of Islamic Educational Institutions. This is based on the development of Islamic educational institutions carried out, including: 1) The establishment of the Generasi Amanah Madani Foundation; 2) Actively and being the main pioneer as a mover in developing Islamic educational institutions, such as: Chairperson of the Community Reading Park Forum of Deli Serdang Regency from 2017-2022, Chairperson of the Early Childhood Educators and Education Personnel Association of Deli Serdang Region from 2019-present, Administrator of the PAUD Mother Group of Deli Serdang Regency from 2023-present, Administrator of the Nahdlatul Ulama Branch of Deli Serdang Regency, and Member of the Indonesian PIAUD Lecturers Association from 2019-present. In developing Islamic educational institutions in Deli Serdang, Arie Dwi Ningsih faces various challenges, such as: 1) The low quality of human resources; 2) The lack of equitable distribution of educational infrastructure; 3) The weak management of Islamic educational institutions; 4) The lack of community support; 5) Technological advancements; 6) The moral decadence of students.